Pemanfaatan Media Sosial Instagram dan Tiktok sebagai Sarana Informasi dan Promosi Sanggar Mahligai Kabupaten Siak Provinsi Riau - Viona Saskia Lestari; Laila Fitriah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This study is motivated by the rapid development of digital technology, which has positioned social media as an essential tool for disseminating information and conducting promotion, including in the field of arts and culture. Sanggar Mahligai in Siak Regency, as an institution dedicated to preserving Malay traditional dance, utilizes social media to expand its informational reach, attract public interest, and maintain the existence of traditional arts amid modern lifestyle changes. This research aims to describe how social media is used as a medium for information dissemination and promotion by Sanggar Mahligai. The study employs a descriptive qualitative method through observation, interviews, and documentation involving the head of the sanggar, social media administrators, and followers of the sanggar’s social media accounts. The findings show that Instagram and TikTok serve as the main platforms for sharing information related to training schedules, performance activities, new member registration, and activity documentation. Visual content, the use of trending formats, and active interaction with the audience significantly increase public engagement and interest in the sanggar’s activities. These results indicate that social media plays an important role in strengthening the sanggar’s visibility, fostering two-way communication, and supporting the preservation of Malay cultural arts through consistent and strategic digital practices.